Edukasi Gizi Efektif Meningkatkan Pengetahuan Atlet Mengenai Gizi Seimbang dan Pemenuhan Kebutuhan Cairan - Puspaningtyas, Desty Ervira; Sari, Siska Puspita; Afriani, Yuni; Mukarromah, Nurul (Jurnal Pengabdian Dharma Bakti, 2019)
Balanced diet is an eating patternthat focuses on the type of food eatenby person, including staple foods, animal protein and vegetable protein, vegetables and fruits. Application of balanced diet accompanied by the fulfillment of fluid needs in athletes has a role supporting the athletes’ performance. However, many athletes have not understood the urgency of balanced diet and the fulfillment of fluid requirements in improving athlete's performance yet. Nutrition education is a solution that can be used to improve the athlete's knowledge about the urgency of balanced diet and fluid requirements fulfillment. Community devotion done to increase athletes’ knowledgewas nutrition education about balanced diet and fluid requirements. Nutrition education performed to 21 soccer athletes at Sekolah Sepak Bola (SSB) Real Madrid on May 08, 2018 at the Stadium of Universitas Negeri Yogyakarta. There was an increase of athlete knowledge between preeducation (56,67 ± 18,33) and post-education (75,24 ± 14,70), with p-value <0,001. Nutrition education can increase athletes' knowledge about balanced nutrition and fluid requirements effectively.Keywords: nutrition education, balanced diet, fluid requirement, knowledge, soccer